Pharmacovigilance As An Important Tool For Reducing Adverse Drug Reactions. - Nagargoje, R. J. (Journal of Neonatal Surgery, 2025)
Before a drug being marketed or made available to the patient clinical trials of the drugs is carried out to check its safety and efficacy, whether it produces any adverse event or serious adverse drug reactions (SADRs), how well the drug works, it’s benefit-harmful profile, Is it producing more harmful effect than benefits, by the manufacturer and If a drug passes the clinical trials it can be marketed. Despite these clinical trials various unexpected and serious adverse drug reactions (SADRs) repeatedly occur after marketing. This study of adverse drug reactions (ADRs) is pharmacovigilance. Pharmacovigilance is the pharmacological science relating to the detection, assessment, understanding and prevention of adverse effects particularly long term and short-term side effects of medicines8. The pharmacovigilance aim is to provide the benefit, effectiveness, safety, harm, risks of medicines on patients, as well as safeguard the rights, safety and wellbeing of all patients in relation to use of medicines. If the drug marketed is found to contain significant toxic effect or serious adverse drug reactions (SADRs) the drug is withdrawn from market or restricted to certain uses. If it is safe, then marketed overall. The international collaboration in the field of pharmacovigilance involves WHO international drug monitoring program which record and report adverse effect of drugs in patient. The proper database management of pharmacovigilance study to meet public expectations and the demands of modern public health1..